2022
DOI: 10.3389/fgene.2022.887582
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selection Signals on the X-Chromosome in East Adriatic Sheep: A New Complementary Approach

Abstract: Sheep are one of the most important livestock species in Croatia, found mainly in the Mediterranean coastal and mountainous regions along the East Adriatic coast, well adapted to the environment and mostly kept extensively. Our main objective was therefore to map the positive selection of the X-chromosome (18,983 SNPs that passed quality control), since nothing is known about the adaptation genes on this chromosome for any of the breeds from the Balkan cluster. Analyses were performed on a sample of eight nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…A number of studies have identified ROH hotspots to be sites of positive selection (Grilz-Seger et al 2019 ; Peripolli et al 2018 ; Purfield et al 2017 ; Sabeti et al 2002 ; Shihabi et al 2022 ). When accounting for the influence of recombination rate, the red deer population on Rum showed five genomic regions with a ROH in more than 15% of the population (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have identified ROH hotspots to be sites of positive selection (Grilz-Seger et al 2019 ; Peripolli et al 2018 ; Purfield et al 2017 ; Sabeti et al 2002 ; Shihabi et al 2022 ). When accounting for the influence of recombination rate, the red deer population on Rum showed five genomic regions with a ROH in more than 15% of the population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). It can be assumed that positive selection leads to a sudden decrease in haplotype diversity (Shihabi et al 2022 ), as certain haplotypes are being favoured. This assumption is also supported by our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified ROH hotspots to be sites of positive selection (Grilz-Seger et al , 2019; Peripolli et al , 2018; Purfield et al , 2017; Sabeti et al , 2002; Shihabi et al , 2022). When accounting for the influence of recombination rate, the red deer population on Rum showed five genomic regions with a ROH in more than 15% of the population (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a sharp decrease in haplotype diversity at the onset of these two ROH hotspots (Figure 3). It can be assumed that positive selection leads to a sudden decrease in haplotype diversity (Shihabi et al , 2022), as certain haplotypes are being favoured. This assumption is also supported by our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that Balkan breeds are evolutionary connected with the domestication process and are one of the hub regions from which the migration of sheep spread to the rest of Europe. Recently, Shihabi et al (2022) identified specific adaptive selection signals on the X chromosome of the individuals used in this analysis.…”
Section: Introductionmentioning
confidence: 99%